Impact of financial flows on human development and income inequality in Asean countries - Abu Hassan, Siti Nurathirah (2021)
International financial flows like remittance and foreign direct investment (FDI) have been important elements of development strategy for many countries including the South East Asian countries. The general objective of this study is to evaluate the impact of financial flows on economic development in the South East Asian region. Specifically, the first objective of this study is to examine the impact of remittance inflows on human development in selected East Asian countries (i.e. Indonesia, Malaysia, the Philippines, and Thailand) over the 1990 to 2019 period. The results based on panel estimators reveal that remittance inflows have a positive impact on human development. Additionally, financial development also appears to be important determinants of human development in the region. The second objective of this study is to investigate whether FDI inflows in the region play any role in reducing income inequality. Using a sample of ASEAN-5 countries (i.e. Indonesia, Malaysia, the Philippines, Singapore and Thailand) over the 1975-2017 period, the results obtained using Pool Mean Group (PMG) estimator reveal that FDI inflows has actually widened income inequality in the region. Interestingly, government expenditure appears to have significant influences in reducing income inequality. Therefore, policymakers should devise a specific policy which deliver a positive economic impact of remittance and FDI inflows in the region